Creative sport marketing communications - the case of Atletico de Madrid - Robles Gonzales, German (Henry Stewart Talks, 2008)
Examination of the creative way in which Atletico de Madrid has used a marketing campaign to promote the club, The campaign aimed at helping to boost attendances while accentuating the nature of the club's brand and fans associated with it, This campaign won major marketing awards
Archived at 2022/04/04